Experience of 300 Cases of Prenatal Fetoscopic Open Spina Bifida Repair: Report of the International Fetoscopic Neural Tube Defect Repair Consortium. Issue 3 (24th September 2022) - Sanz Cortes, M.; Chmait, R.H.; Lapa, D.A.; Belfort, M.A.; Carreras, E.; Miller, J.L.; Brawura Biskupski Samaha, R.; Sepulveda Gonzalez, G.; Gielchinsky, Y.; Yamamoto, M.; Persico, N.; Santorum, M.; et al.
Abstract : ( Am J Obstet Gynecol . 2021;225:678.e1–678.e11. [Epub June 3, 2021]) Prenatal repair of open spina bifida (OSB) showed increased chance of independent ambulation and increased outcomes of ventriculoperitoneal shunting compared with postnatal repair in a multicenter randomized controlled trial in the Management of Myelomeningocele Study (MOMS). The technique, involving a hysterotomy, has risks regarding the uterine incision used. Due to the risks, fetal surgeons worldwide have been attempting to repair OSB using minimally invasive techniques to mitigate adverse outcomes and improve neonatal neurologic benefits. One such technique is fetoscopic OSB repair.